A new species of Scoloposcelis Fieber (Hemiptera: Heteroptera: Anthocoridae: Scolopini) from the Korean Peninsula, with a key to the Palaearctic species - Jung, Sunghoon; Yamada, Kazutaka; Lee, Seunghwan (Zootaxa, 2011)
One new species of flower bug, Scoloposcelis koreanus Jung & Yamada, sp. nov., that inhabits shiitake mushroom farms, is described from Gangwon-do Province, South Korea. Diagnosis, description and biological notes of the new species are presented, along with a key to the species of Scolopocelis from the Palaearctic Region.